A low frequency tunable hybrid generator - Salim M.D.; Salleh H.; Salim D.S. (2023)
A serious of experimental tests on a commercial brass reinforced PZ bimorph cantilever of the type 5H4E were carried out in a vibration laboratory using a Labview of NI make as instrumentation and control system. Originally the bender acted as a tunable PZ generator, using perforated steel shims as a proof mass. The generator was converted to a hybrid generator by adding ring magnets to its other surface and making them working as part of an electromagnetic generator in addition of being a proof mass. Two arrangement of the electromagnetic generator were investigated at a frequency of (33) Hz which is the resonance frequency at max power of the original PZ generator. By using a shaker the cantilever was vibrated and set into acceleration of (0.25) g rms during all stages as this value was considered to be available and acceptable in balanced large rotating machines in industry. The hybrid generator produced (187) ?W for max power, (14.8) Vrms for max OCV, and (8.26) Vrms for max on load voltage for the PZ part, while the electromagnetic part produced max (70) Vrms, (490) ?W for arrangement (1) and (34) V rms, (116) ?W for arrangement (2) on no load condition and at the same frequency. The experimental results obtained from the electromagnetic generator are acceptable compared with theory. 2013 Springer-Verlag Berlin Heidelberg.